Plagiorchis sp. in small mammals of Senegal and the potential emergence of a zoonotic trematodiasis. (April 2019) - Catalano, Stefano; Nadler, Steven A.; Fall, Cheikh B.; Marsh, Kirsty J.; Léger, Elsa; Sène, Mariama; Priestnall, Simon L.; Wood, Chelsea L.; Diouf, Nicolas D.; Bâ, Khalilou; Webster, Joanne P.
Abstract: Trematodes of the genus Plagiorchis have a wide geographical distribution and can exploit a variety of hosts. The occurrence and zoonotic potential of Plagiorchis spp. have been characterised across several countries in Asia; in contrast, information on Plagiorchis parasites in Africa remains anecdotal. We isolated a previously undescribed Plagiorchis species from the biliary tract and small intestine of 201 out of 427 small mammals collected in the region of Lake Guiers, Senegal, with local prevalence ranging from 38.6% to 77.0%. Conversely, Plagiorchis isolates were not observed in the 244 small mammals sampled in and around the town of Richard Toll, Senegal. Molecular phylogenetics of the internal transcribed spacer region, nuclear ribosomal DNA, and of the cytochrome c oxidase subunit 1 gene, mitochondrial DNA, supported the monophyly and multi-host spectrum of this newly discovered West African Plagiorchis species. Sequencing of individual cercariae shed by Radix natalensis (Gastropoda: Lymnaeidae) suggested that these freshwater snails may act as suitable first intermediate hosts. Phylogenetic analysis yielded a highly resolved topology indicating two different clades, one composed by Plagiorchis spp. infecting rodents, insectivores, and birds, while the other included parasites of bats. Our findings showed the low host specificity and high prevalence of the isolated Plagiorchis sp. in the Lake Guiers region, with Hubert's multimammate mice ( Mastomys huberti ) appearing to play a primary role in the epidemiology of this parasite. The results raise concern about the zoonotic potential of Plagiorchis sp. in local communities of the Lake Guiers region, and highlight food-borne trematodiases and their link to land-use change as a neglected public health issue in regions of West Africa. Graphical abstract: Image 1 Highlights: Monophyletic, previously undescribed Plagiorchis lineage in African small mammals. High local prevalence ranging from 38.6% to 77.0% in the examined hosts. Identification of the gastropod Radix natalensis as first intermediate host. Potential role of Plagiorchis sp. as emerging zoonotic pathogen in northern Senegal.